CD24 blunts the sensitivity of retinoblastoma to vincristine by modulating autophagy. Issue 8 (13th June 2020) - Sun, Jie; Feng, Dongju; Xi, Huiyu; Luo, Jiajing; Zhou, Zewei; Liu, Qinghuai; Chen, Yun; Shao, Qing
Abstract : Retinoblastoma (RB) is the most common childhood malignant intraocular tumor. The clinical efficacy of vincristine (VCR) in the treatment of RB is severely limited by drug resistance. Here, we found that CD24, a GPI‐anchored protein, was overexpressed in human RB tissues and RB cell lines, and was associated with the sensitivity of RB cells in response to VCR therapy. We demonstrated that CD24 plays a critical role in impairing RB sensitivity to VCR via regulating autophagy. Mechanistically, CD24 recruits PTEN to the lipid raft domain and regulates the PTEN/AKT/mTORC1 pathway to activate autophagy. Lipid raft localization was essential for CD24 recruitment function. Collectively, our findings revealed a novel role of CD24 in regulating RB sensitivity to VCR and showed that CD24 is a potential target for improving chemotherapeutic sensitivity and RB patient outcomes. Abstract : Chemotherapy failure is the major cause of recurrence and poor prognosis in retinoblastoma (RB) patients. We found that CD24 is overexpressed in human RB tissues and RB cell lines, and is associated with the sensitivity of RB cells to VCR therapy. CD24, a GPI‐anchored protein linked to membrane lipid raft microdomains, recruits PTEN to the lipid raft domain and regulates the PTEN/AKT/mTORC1 pathway to activate autophagy. Our study shows that CD24 blunts the sensitivity of RB to VCR via activating autophagy.